2021
DOI: 10.1123/jmld.2020-0056
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Assessment of Overarm Throwing in Children With and Without Developmental Coordination Disorder

Abstract: Background: Children with developmental coordination disorder (DCD) frequently have difficulties performing gross motor skills such as the overarm throw. Our study examines the differences in both qualitative and quantitative characteristics of overarm throwing for accuracy between typically developing (TD) and children with DCD. Methods: A total of 74 children (36 females/38 males) aged between 7 and 11 years, participated in this study. The authors used the Movement Assessment Battery for Children—second edi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…We found that males had more advanced throwing technique than females initially and throughout the study, irrespective of their group membership. As such, our hypothesis that males would throw with more advanced technique than females was supported, a finding that is consistent with prior studies that examined gender differences in throwing both quantitatively (e.g., throwing velocity and distance) and qualitatively (Gromeier et al, 2017;Johnson et al, 2020;Lorson et al, 2013;Schott & Getchell, 2021). On average, males have been found to throw with more accuracy, velocity, and advanced technique than females at all ages.…”
Section: Gender Differencessupporting
confidence: 89%
“…We found that males had more advanced throwing technique than females initially and throughout the study, irrespective of their group membership. As such, our hypothesis that males would throw with more advanced technique than females was supported, a finding that is consistent with prior studies that examined gender differences in throwing both quantitatively (e.g., throwing velocity and distance) and qualitatively (Gromeier et al, 2017;Johnson et al, 2020;Lorson et al, 2013;Schott & Getchell, 2021). On average, males have been found to throw with more accuracy, velocity, and advanced technique than females at all ages.…”
Section: Gender Differencessupporting
confidence: 89%
“…As skill learning progresses, this will result in greater flexibility in the way children move their limbs to successfully accomplish a task. Such adaptability allows skilled performers to execute a task in different initial conditions and changing environmental constraints [48].…”
Section: Clinical Implicationmentioning
confidence: 99%